Scheduling Jobs and a Variable Maintenance on a Single Machine with Common Due-Date Assignment - Long Wan (The Scientific World Journal)
We investigate a common due-date assignment scheduling problem with a variable maintenance on a single machine. The goal is to minimize the total earliness, tardiness, and due-date cost. We derive some properties on an optimal solution for our problem. For a special case with identical jobs we propose an optimal polynomial time algorithm followed by a numerical example.